VD_FINDINFO Jug / 2009 / 69 vom 15. Dezember 2009 - VD Tribunal cantonal (2009)
CONTRAT D'ARCHITECTE, HONORAIRES, OBLIGATION DE RENSEIGNER, LUCRUM CESSANS, CAUSALITÉ ADÉQUATE | 102 CO, 104 al. 1 CO, 321e CO, 364 al. 1 CO, 394 al. 3 CO, 398 CO, 403 CO, 97 CO, 266 al. 1 CPC, 268 al. 1 CPC, 302 CPC